Low level or absent in vivo replication of hepatitis C virus and hepatitis G virus/GB virus C in peripheral blood mononuclear cells - Mellor, J; Haydon, G; Blair, C; Livingstone, W; Simmonds, P (Journal of general virology, 1998)
J Mellor, G Haydon, C Blair, W Livingstone and P Simmonds Department of Medical Microbiology, University of Edinburgh, UK. To investigate which subsets of peripheral blood mononuclear cells (PBMCs) are susceptible to infection with hepatitis C virus (HCV) and hepatitis G virus (HGV) or GB virus C (GBV-C), a PCR-based assay using tagged primers in the core region (HCV) and NS3 region (HGV/GBV-C) for the specific detection of negative strand (replicating) viral RNA sequences was developed. In liver biopsy samples both positive and negative strands of HCV RNA were detected, at levels ranging from 3 to 11 x 10(6) RNA copies per 10(6) cells and 3.7-4.2 x 10(3) copies per 10(6) cells respectively, while lower frequencies of positive strands of GBV-C/HGV RNA were detected (from 13 biopsies, the highest frequency was 7.3 x 10(3) per 10(6) cells). In no samples were negative RNA strands detected. To investigate extra-hepatic replication of HCV and GBV-C/HGV, CD4+, CD8+ and B lymphocytes, monocytes and putative dendritic cell populations were separated from PBMCs from ten study subjects. Detection of positive strand HCV RNA was largely confined to B lymphocytes (at levels of up to 5 x 10(3) copies per 10(6) cells), while detection of negative strands was confined to a single subset (dendritic cells) of one of the study individuals. Similarly, GBV-C/HGV was detected at low levels in only twelve of twenty PBMC samples, while negative strands were uniformly absent. The low levels of HCV and GBV- C/HGV RNA in PBMCs suggest that these cells are at most a minor reservoir for virus replication. The absence of detectable replication of GBV-C/HGV suggests that the actual site of GBV-C/HGV replication remains to be discovered.